Puerto Intermedio de Transporte Operativo Natural (PITON) (2020)
The Amazon region covers much of Colombia's territory, around 40%, while being the least populated region of the country. It has two opposing characteristics that define it, the first being its great environmental and cultural wealth, the second is vulnerability to its soils and its population. The work area is delimited in the Amazonian trapeze taking into account its environmental conservation status and its border location, the place of intervention for the development of the master plan is based on the inaccessibility with the country and the vulnerability generated by the lack of control and environmental, cultural, social aid, the connection would be given by the Putumayo river directly connected to the Corregimiento de Tarapacá and in this way it would relate to the only two municipalities and consolidated urban centers of the sector, Leticia and Puerto Nariño, to address environmental and social vulnerability are intended to generate point units of action that serve as a model for an impact throughout the region.